Development of an Assessment Scale for Commencing Home-Visit Nursing in Japan: Examining the Construct. Issue 3 (August 2019) - Shimohigoshi, Naoko; Yatsushiro, Rika
This study examined the assessment criteria based on which care managers (CMs) decide to commence home-visit nursing to develop a common assessment scale to guide CMs in making sound decisions about whether to commence home-visit nursing. For this purpose, we conducted a postal survey of 200 CMs. After removing 17 items from the questionnaire based on item analysis, we analyzed the remaining factors to confirm construct validity. This factor analysis identified 96 items comprising the following four factors: (1) the daily life condition of users and the support required by them, (2) strengthening medical support, (3) scheduling medical treatment/management or recuperation, and (4) preparing for users' mental and physical changes and preventing the deterioration of the situation. The results of the study indicate the first step in the process of developing a common assessment scale; in this study, we clarified the general factors that underpin a decision to commence home-visit nursing and the relationships among the items for each factor.